PERAN BADAN USAHA MILIK DESA (BUMDES) DALAM MENINGKATAN PENDAPATAN MASYARAKAT DI DESA SATRIA KECAMATAN MOOTILANGO KABUPATEN GORONTALO - Apris Ara Tilome; Ramlah Alkatiri; Agustin Djafar (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2020)
The objective of research was to determine the roles of BUMDES in increasing the communities’ income at satria village. The method used qualitative approach with descriptive research. The result obtained the government roles, BUMDES management in terms of socialization has been carried out optimally, there are already people who are satisfied and there are still those who are not satisfied with the active role of BUMDES, the government and administrators have made efforts in realizing and developing BUMDES to improve the community's economy by collaborating with certain parties, especially related agencies, the income of the community, especially BUMDES members, has increased with the establishment of BUMDES in the village and the benefits of BUMDES are felt by the community despite the existence of BUMDES can still be said to be just operating.